State consent in the spotlight: a current analysis on its legal nature, its enforcement to international justice and the importance attached to it within International Law - de Trazegnies Valdez, Carlos Fernando (2023)
This paper focuses on state consent as a central and fundamental concept within International Law. It addresses its general legal nature, its relationship with principles of International Law such as the pacta sunt servanda, consuetudo est servanda and good faith; and its classification according to the doctrine. It rigorously defines the concept and its effects in the international sphere.Likewise, the author analyses state consent from the perspective of International Procedural Law, particularly from the perspective of the International Court of Justice. In this regard, he addresses the modalities of access to the jurisdiction of the International Court of Justice, as well as the prerogatives it has to find itself to be competent in relation to the consent of the parties.Finally, this paper proposes an analysis on the case of the Arbitral Award of 1899, between Guyana and Venezuela, based on the relativization of state consent at the hands of the International Court of Justice. It is concluded, in this regard, that the Court created a mistake by attempting to analyze whether the consent expressed by the States had been unequivocal.